Drill, discipline and decency? Exploring the significance of prior military experience for prison staff culture - Moran, Dominique (Theoretical criminology, 2022)
Building on prior theorization of the prison–military complex and critiques of Foucault’s claim of similarities between the prison and the military, this article uses the example of ex-military personnel as prison staff to consider the nature of this relationship. In a UK context in which policy discourse speaks of ‘military’ methods as an aspiration for the Prison Service but where critical prison scholars use this term more pejoratively, it draws on a unique survey of current and former prison staff to explore the perceived characteristics of ex-military personnel, and the relationship between military service and prison staff culture. The article finds that although some ‘military’ characteristics recall more negative ‘traditional’ cultures, others point towards more professional and compassionate attitudes, challenging the notion that ‘militarism’ necessarily engenders authoritarian and punitive prison regimes.